2013
DOI: 10.4314/njbas.v21i1.7
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Effect of the Aqueous Leaf Extract of Andrographis paniculata Nees Against Carbon Tetrachloride – Induced Hepatotoxicity in Rats

Abstract: Hepatoprotective effect of the aqueous leaf extract of Andrographis paniculata was investigated against CCl4 -induced hepatic injury in rats. Significant (P<0.05) increase of serum levels of alanine aminotransferase (ALT), aspartate amino transferase (AST), alkaline phosphatase (ALP), total bilirubin (TBL), direct bilirubin (DBL), total cholesterol (CHL), triglycerides (TG), low density lipoprotein (LDL), very low density lipoprotein (VLDL) and malondialdehyde (MDA) in CCl4 intoxicated rats were restored to no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 43 publications
2
15
1
Order By: Relevance
“…On the other hand, by increasing HDL production and decreasing LDL production, it facilitates the breakdown of acetate by liver. These findings of our study were consistent with the findings of other studies [32] , [29] , [34] .…”
Section: Discussionsupporting
confidence: 94%
“…On the other hand, by increasing HDL production and decreasing LDL production, it facilitates the breakdown of acetate by liver. These findings of our study were consistent with the findings of other studies [32] , [29] , [34] .…”
Section: Discussionsupporting
confidence: 94%
“…These results were in a harmony with many studies; Nasir et al, (42) who reported that the treatment with Andrographolide show reduction in the levels of ALT and AST towards the normal value is an indication of regeneration process. Chen et al, (29) reported that Andrographolide decrease activity of ALT and AST.…”
Section: Discussionsupporting
confidence: 90%
“…The antidiabetic effects of A. paniculata have been investigated by number of researchers from in silico studies to human evidence (Kooti et al, 2016;Niranjan et al, 2010;Nizmawardini et al, 2013;Xu et al, 2007Xu et al, , 2010. It has also a wide range of pharmacological effects (Akhtar et al, 2016;Jayakumar et al, 2013;Rajasekaran et al, 2016), including hepatoprotective (Nasir et al, 2013;Vetriselvan and Middha, 2016), antioxidant (Dandu and Inamdar, 2009), and anti-inflammatory (Zou et al, 2016), which are beneficial for people with T2DM, since it may help minimize complications of diabetes. On the other hand, Syzygium polyanthum (Wight.)…”
Section: Introductionmentioning
confidence: 99%